SYNTАGMАTIСS ОF ОССАSIОNАL РHRАSЕОLОGIСАL DЕRIVАTIVЕS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the syntagmatics of occasional phraseological derivatives, exploring their formation, structure, and contextual usage in language. It highlights the interplay between linguistic norms, individual creativity, and communicative intentions in shaping these occasional expressions. Drawing from linguistic theories and examples, the study emphasizes the nuanced meanings and functional characteristics of occasional phraseological units compared to their conventional counterparts. The analysis also touches upon the role of context, creativity, and communicative strategies in the construction and interpretation of these linguistic constructs, shedding light on their dynamic nature within discourse.